2003
DOI: 10.4141/p01-098
|View full text |Cite
|
Sign up to set email alerts
|

The biology of Canadian weeds. 118. Artemisia vulgaris L.

Abstract: is an introduced rhizomatous perennial found primarily along roadsides, in waste areas, and in non-containerized nursery crops in eastern regions of Canada and the United States. Artemisia vulgaris is rapidly spreading throughout the Northern Hemisphere, and is currently found in nine Canadian provinces, as well as half of the states in the United States. Historically, A. vulgaris has been used as an herbal remedy and for flavouring beer, but recently has been identified as a primary pest of nurseries and urba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
66
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 23 publications
(29 reference statements)
0
66
0
1
Order By: Relevance
“…This species is the most common infestations occur in Europe, where it is thought to have originated, but this weed is also found in Southeastern Asia, Australia, and South America [9]. A. vulgaris has been used as an herbal remedy and for flavouring beer, but recently has been identified as a primary pest of nurseries and urban landscapes [19]. It is characterized by its white-woolly hairs on the lower leaf surface and the presence of a dense underground rhizome system also by its undivided, wedged-shaped leaves, each with three blunt lobes [ 20] (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This species is the most common infestations occur in Europe, where it is thought to have originated, but this weed is also found in Southeastern Asia, Australia, and South America [9]. A. vulgaris has been used as an herbal remedy and for flavouring beer, but recently has been identified as a primary pest of nurseries and urban landscapes [19]. It is characterized by its white-woolly hairs on the lower leaf surface and the presence of a dense underground rhizome system also by its undivided, wedged-shaped leaves, each with three blunt lobes [ 20] (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Out of them, common mugwort is being studied as a possible source for food and pharmaceutical industry in Lithuania and other countries (Judžentienė and Buzelytė, 2006). In traditional agriculture, mugwort is considered as a weed with the ability to propagate easily from small rhizome fragments (Barney and DiTommaso, 2003). It has been reported that Artemisia genus energy value can reach up to 4500 kcal kg -1 (Van Epps et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Artemisia genus species are widespread in many countries around the world (Barney and DiTommaso, 2003). Out of them, common mugwort is being studied as a possible source for food and pharmaceutical industry in Lithuania and other countries (Judžentienė and Buzelytė, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…comm.). It was introduced to North America (Holm et al, 1997;El-Sahhar et al, 2010) where it became a noxious weed in nursery crops, often occurring along roadsides and is widespread in waste areas (Barney and DiTomasso, 2003). Mugwort is a rhizomatous perennial weed locally reproduced by rhizomes.…”
mentioning
confidence: 99%
“…At the end of the growing season ramification occurs and branches develop accommodating flower spikes (Holm et al, 1997). The rhizomes branching at the nodes and reaching depths of 7-18 cm in the soil (Barney and DiTomasso, 2003). Mugwort is native to Europe, it can be found along roadsides, and in waste areas, it cannot stand the soil cultivation of the arable crops (Kazinczi, 2016 pers.…”
mentioning
confidence: 99%